Is there still a role for nuchal translucency measurement in the changing paradigm of first trimester screening?. (27th November 2019) - Bardi, Francesca; Bosschieter, Pien; Verheij, Joke; Go, Attie; Haak, Monique; Bekker, Mireille; Sikkel, Esther; Coumans, Audrey; Pajkrt, Eva; Bilardo, Caterina
Abstract: Objectives: To give an overview of the genetic and structural abnormalities occurring in fetuses with nuchal translucency (NT) measurement exceeding the 95th percentile at first‐trimester screening and to investigate which of these abnormalities would be missed if cell‐free fetal DNA (cfDNA) were used as a first‐tier screening test for chromosomal abnormalities. Methods: This is a national study including 1901 pregnancies with NT≥95th percentile referred to seven university hospitals in the Netherlands between 1 January 2010 and 1 January 2016. All cases with unknown pregnancy outcome were excluded. Results of detailed ultrasound examinations, karyotyping, genotyping, pregnancy and neonatal outcomes, investigation by a clinical geneticist and post‐mortem investigations were collected. Results: In total, 821 (43%) pregnancies had at least one abnormality. The rate of abnormalities was 21% for fetuses with NT between 95 th and 99 th percentile and 62% for fetuses with NT≥99 th percentile. Prevalence of single‐gene disorders, submicroscopic, chromosomal and structural abnormalities was 2%, 2%, 30% and 9%, respectively. Conclusion: Although cfDNA is superior to the combined test, especially for the detection of trisomy 21, 34% of the congenital abnormalities occurring in fetuses with increased NT may remain undetected in the first trimester of pregnancy, unless cfDNA is used in combination with fetal sonographic assessment, including NT measurement. Abstract : What's already known about this topic? Nuchal translucency is associated with a wide range of chromosomal and structural abnormalities. What does this study add? If cell‐free DNA were used as the only first trimester screening test, 34% of fetal congenital abnormalities would be missed in the first trimester of pregnancy. In high‐risk pregnancies with increased nuchal translucency (NT≥95 th percentile), 23% of abnormalities are found in fetuses with NT between 95 th and 99 th percentile.